U.S.S SYSTEM (ULTRASONIC SECURITY SYSTEM), SISTEM KEAMANAN RUANG BERBASIS ULTRASONIK YANG EFEKTIF DAN EFISIEN - Irawan, Hendra; Siddiq, Nur Abdillah; Hamidah, Yusnia Hamidah; Hasyyati, Amalia (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
The advantage of ultrasonic sensors is it is able to secure the safety in dark, low cost, cover all the rooms, and no need operator. The principle is to measure changes in the distance that reflected ultrasonic wave, it will be used as input for the microcontroller (ATMega 16) and output is alarm. There ATMega16, IC Regulator, TIPC, MAX 232, 2 On Button, ultrasonic sensor and servo. Software interface serves as an intermediary between users and hardware to provide a display that is easy to operate. Advantage of USS. System does not require operator so that it can be classified into smart devices.